Hubungan Kecanduan Game Online Pubgm dengan Perilaku Agresi Verbal pada Remaja di Kecamatan Lubuk Basung - Kartika Triyaneva (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The technological growth at the present time is so rapid, one form of technological advancement is an online game. An online game is a game played online using the internet. Young people who play the online game feel that playing an online game will reduce the load of thought gained from the environment. If a youth is dependent on playing online games it will be bad for the teen. So it requires the role of the people around him to monitor and direct the youth away from the negative effects of online gaming. This study aims to determine the relationship between online game addiction and verbal aggression behavior in adolescents in Lubuk Basung District. This study uses quantitative methods with the research design used is correlational test research.The population in this study are teenagers who like to play PUBG online games. The sampling technique used purposive sampling with a total of 103 adolescents who played pubg mobile online games. In collecting data using an online game addiction scale with a verbal aggression scale. The results of data analysis obtained a correlation of sig = 0.137 (sig <0.05). These results show that there is a significant relationship between online game addiction and verbal aggression behavior